Prunus tomentosa Thunb. – A lesser known wild fruit plant genetic resource of Kashmir Himalayas - Sultan, Sheikh M; Raina, Susheel Kumar (Indian Horticulture, 2020)
Prunus tomentosa is a naturalized wild species found in some northern Himalayan regions of India including Kashmir valley. It grows mostly on hill slopes and near foot hills at many places across Kashmir. It bears small nutritious, edible cherry like fruit and has been used as rootstock for peaches, plums and sweet cherries in different parts of the world. Unlike other wild fruits, this important species of Prunus is not so popular despite having a great potential to be developed into a commercial fruit crop for promoting resilience, improving livelihood and supporting food security and nutrition. In this article an attempt has been made to present some important features of this lesser known plant genetic resource of Himalayas.